DE-MORALIZATION AS EMANCIPATION: LIBERTY, PROGRESS, AND THE EVOLUTION OF INVALID MORAL NORMS *. Issue 2 (21st December 2017) - Buchanan, Allen; Powell, Russell
Abstract: Liberal thinkers of the Enlightenment understood that surplus moral constraints, imposed by invalid moral norms, are a serious limitation on liberty. They also recognized that overcoming surplus moral constraints — what we call proper de-moralization — is an important dimension of moral progress. Contemporary philosophical theorists of liberty have largely neglected the threat that surplus moral constraints pose to liberty and the importance of proper de-moralization for human emancipation. This essay examines the phenomena of surplus moral constraints and proper de-moralization, utilizing insights from biological and cultural evolutionary thinking